PERBANDINGAN ESTIMASI BIAYA KOLOM BULAT DENGAN KOLOM PERSEGI PADA GEDUNG MIN 8 KOTA BANDA ACEH - Munir Munir; Muhammad Ridha; Tety Sriana (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Building of State Elementary Islamic School 8 in Banda Aceh City is planned to be constructed for 2-story building with round columns, aiming to get a safe calculation of the structure of round columns and to get a comparison of the estimated costs between round columns and square columns. The scope of this research is to calculate the building structure using the SAP 2000 application. The research process begins with data collection in the form of structural data, building plan drawings, and Budget Plan. The calculation of the spherical column structure in the equation, the floor deviation limit is 12.411 mm < 87.5 mm. Based on the estimated cost between the round column and the square column, the cost is Rp. 180.340.013.34 (One Hundred Eighty Million Three Hundred Forty Thousand Thirteen Rupiah) for round column. Rp. 222.512.998.00 (Two Hundred Twenty Two Million Five Hundred Twelve Thousand Nine Hundred Ninety Eight Rupiah) for square column.Keywords: Round Column, Square Column, Column Steel, Column Comparison, Cost.Gedung MIN 8 Kota Banda Aceh direncanakan 2 lantai dengan kolom berbentuk bulat, bertujuan untuk mendapatkan perhitungan struktur kolom bulat yang aman dan mendapatkan perbandingan estimasi biaya antara kolom bulat dengan kolom persegi. Ruang lingkup penelitian ini adalah menghitung struktur bangunan dengan menggunakan aplikasi SAP 2000. Proses penelitian diawali dengan pengumpulan data berupa data struktur, gambar bestek gedung, dan Rencana Anggaran Biaya (RAB). Perhitungan struktur kolom bulat pada persamaannya batasan simpangan lantai adalah 12,411 mm < 87,5 mm. Berdasarkan estimasi biaya antara kolom bulat dengan kolom persegi maka didapat biaya Rp. 180.340.013.34 (Seratus Delapan Puluh Juta Tiga Ratus Empat Puluh Ribu Tiga Belas Rupiah) untuk kolom bulat. Rp. 222.512.998.00 (Dua Ratus Dua Puluh Dua Juta Lima Ratus Dua Belas Ribu Sembilan Ratus Sembilan Puluh Delapan Rupiah) untuk kolom persegi.Kata Kunci: Kolom Bulat, Kolom Persegi, Pembesian Kolom, Perbandingan Kolom, Biaya.